Does gadget usage hamper the psychological aspects of pre-schoolers? - Hon, Kai Yee; Chua, Bee Seok; Shazia Iqbal Hashmi (IGI Global, 2017)
The society is keen to rely on gadgets in everyday life due to versatile gadgets that help them to connect with the world in the 21st century. On the flip side of using gadgets, several researches argued that screen time is affecting children's psychosocial, behavioural and health problems. The present study interviewed 14 preschool teachers to perceive their knowledge in gadget usage, sedentary behaviour and social skills among preschoolers. Besides that, teaching methods and teachers' opinions on gadget usage were also discussed. Inductive analysis (IA) revealed that parents habitually offer children gadgets at home. Also, the teachers expressed a positive opinion on gadget usage where preschoolers simply learn from media and gadget's applications. However, the teachers asserted that usage time needs to be controlled and the amount of usage depends on the role of parents and teachers. Teachers' attitude and habits were found to be moderate in lesson planning and improving the social skills of preschoolers but minimal for addressing their sedentary behaviour.